Decision Support System for Covid-19 Social Assistance Recipients Applying the Weighted Aggregated Sum Product Assessment Method - Simanjuntak, Deby Monalisa; Mesran (Journal of Decision Support System Research, 2024)
The government's efforts to provide social assistance to fulfil all economic needs for people affected by Covid-19 are not optimal. So that many people feel that the social assistance provided is not right on target. Manual data entry in Medan Estate Village is claimed to be at risk of not being on target, multiple recipients and individuals who take advantage of the situation.  The WASPAS method is expected to determine the criteria for people who are entitled to receive Covid-19 social assistance, because the WASPAS method will carry out a ranking process based on attributes with different weights so that the results are more optimal. This research is to find the weight value for each attribute, then a ranking process is carried out which will determine the optimal alternative in receiving social assistance. The 5 alternatives that are the results of determining the recipients of Covid-19 Social Assistance are alternative A2 with a result of 0.7553, A1 with a result of 0.7198, A6 with a result of 0.6159, A11 with a result of 0.6086 and A8 with a result of 0.5999.